Neck pain among smartphone users: an imminent public health issue during the pandemic time - Mathew K V, Binoy; Walarine, Maryelizabeth Tidiya (Journal of Ideas in Health, 2020)
COVID-19 Pandemic resulted in social mobility and travel restrictions to contain the infection. It has been reported that there happened post-pandemic surge in the use of the internet and social media as people rely on it more often for entertainment, work, and learning purposes. It is also been used as an unhealthy coping strategy for pandemic related stress. The smartphone was found to be the most common gadget used for accessing internet-based services. Owing to the postural alterations related to the small screen size of smartphones, neck pain was reported very commonly among smartphone users. Neck pain among smartphone users is a public health concern needing immediate attention in the pandemic time. Many of the risk factors leading to neck pain among smartphone users are modifiable. The authors outline preventive strategies that are mostly self- regulated. The strategies recommended include reducing Smartphone usage time (Smartphone-Free Time, Smartphone-Free Zone), maintaining ideal posture (Focus Breaks, Mobility Breaks, How am I keeping my posture?, Hands-free alternatives), doing regular exercises, preparing and following an activity schedule, and inculcating healthy habits. References Sohrabi C, Alsafi Z, O’Neill N, Khan M, Kerwan A, Al-Jabir A, et al. World Health Organization declares global emergency: A review of the 2019 novel coronavirus (COVID-19). Int J Surg 2020; 76: 71–6. https://doi.org/10.1016/j.ijsu.2020.02.034 Király O, Potenza MN, Stein DJ, King DL, Hodgins DC, Saunders JB, et al. Preventing problematic internet use during the COVID-19 pandemic: Consensus guidance. Compr Psychiatry 2020; 100:152180. https://doi.org/10.1016/j.comppsych.2020.152180 Sun Y, Li Y, Bao Y, Meng S, Sun Y, Schumann G, et al. Brief Report: Increased Addictive Internet and Substance Use Behavior During the COVID‐19 Pandemic in China. Am J Addict 2020 ;29(4):268–70. https://doi.org/10.1111/ajad.13066 Varga E. How does the Internet Influences the Readers’ Behavior. Procedia Manuf. 2020; 46:949–56. https://doi.org/10.1016/j.promfg.2020.05.013 Zhuang L, Wang L, Xu D, Wang Z, Liang R. Association between excessive smartphone use and cervical disc degeneration in young patients suffering from chronic neck pain. J Orthop Sci. 2020; https://doi.org/1016/j.jos.2020.02.009 Davey S, Davey A. Assessment of smartphone addiction in indian adolescents: a mixed method study by systematic-review and meta-analysis approach. Int J Prev Med.2014;5(12):1500–11. Available from: http://www.ncbi.nlm.nih.gov/pubmed/25709785 Smetaniuk P. A preliminary investigation into the prevalence and prediction of problematic cell phone use. J Behav Addict 2014 Mar;3(1):41–53. https://doi.org/1556/JBA.3.2014.004 Lee H, Seo MJ, Choi TY. The Effect of Home-based Daily Journal Writing in Korean Adolescents with Smartphone Addiction. J Korean Med Sci. 2016;31(5):764. https://doi.org/3346/jkms.2016.31.5.764 Yu S, Sussman S. Does Smartphone Addiction Fall on a Continuum of Addictive Behaviors? Int J Environ Res Public Health.2020;17(2):422. https://doi.org/10.3390/ijerph17020422.10. Kwon M, Kim D-J, Cho H, Yang S. The smartphone addiction scale: development and validation of a short version for adolescents. PLoS One2013;8(12): e83558. https://doi.org/1371/journal.pone.0083558 Ding D, Li J. Smartphone Overuse – A Growing Public Health Issue. J Psychol Psychother.2017;07(289):1-3. https://doi.org/0.4172/2161-0487.1000289 Boumosleh JM, Jaalouk D. Depression, anxiety, and smartphone addiction in university students- A cross sectional study. PLoS One 2017;12(8): e0182239. https://doi.org/1371/journal.pone.0182239 Xie Y, Szeto G, Dai J. Prevalence and risk factors associated with musculoskeletal complaints among users of mobile handheld devices: A systematic review. Appl Ergon.2017 Mar;59:132–42. https://doi.org/1016/j.apergo.2016.08.020 Alsalameh AM, Harisi MJ, Alduayji MA, Almutham AA, Mahmood FM. Evaluating the relationship between smartphone addiction/overuse and musculoskeletal pain among medical students at Qassim University. J Fam Med Prim care. 2019;8(9):2953–9. https://doi.org/4103/jfmpc.jfmpc_665_19 Toh SH, Coenen P, Howie EK, Smith AJ, Mukherjee S, Mackey DA, et al. A prospective longitudinal study of mobile touch screen device use and musculoskeletal symptoms and visual health in adolescents. Appl Ergon. 2020; 85:103028. https://doi.org/1016/j.apergo.2019.103028 Lee S, Kang H, Shin G. Head flexion angle while using a smartphone. Ergonomics. 2015 Feb 17;58(2):220–6. https://doi.org/1080/00140139.2014.967311 Guan X, Fan G, Chen Z, Zeng Y, Zhang H, Hu A, et al. Gender difference in mobile phone use and the impact of digital device exposure on neck posture. Ergonomics. 2016;59(11):1453–61. https://doi.org/10.1080/00140139.2016.1147614 Han H, Shin G. Head flexion angle when web-browsing and texting using a smartphone while walking. Appl Ergon. 2019; 81:102884. https://doi.org/1016/j.apergo.2019.102884 Singla D, Veqar Z. Association between forward head, rounded shoulders, and increased thoracic kyphosis: a review of the literature. J Chiropr Med. 2017;16(3):220–9. https://doi.org/1016/j.jcm.2017.03.004 Park J-H, Kang S-Y, Lee S-G, Jeon H-S. The effects of smart phone gaming duration on muscle activation and spinal posture: Pilot study. Physiother Theory Pract. 2017;33(8):661–9. https://doi.org/10.1080/09593985.2017.1328716 Xie Y, Szeto GPY, Dai J, Madeleine P. A comparison of muscle activity in using touchscreen smartphone among young people with and without chronic neck–shoulder pain. Ergonomics. 2016;59(1):61–72. https://doi.org/10.1080/00140139.2015.1056237 Hansraj KK. Assessment of stresses in the cervical spine caused by posture and position of the head. Surg Technol Int. 2014; 25:277–9. Li W, Yang Y, Liu Z-H, Zhao Y-J, Zhang Q, Zhang L, et al. Progression of mental health services during the COVID-19 outbreak in China. Int J Biol Sci. 2020;16(10):1732–8. https://doi.org/7150/ijbs.45120 Namwongsa S, Puntumetakul R, Neubert MS, Boucaut R. Factors associated with neck disorders among university student smartphone users. Work. 2018;61(3):367–78. https://doi.org/3233/WOR-182819 Ko P-H, Hwang Y-H, Liang H-W. Influence of smartphone use styles on typing performance and biomechanical exposure. Ergonomics. 2016;59(6):821–8. https://doi.org/10.1080/00140139.2015.1088075